Anemia in pregnancy: a systematic review and meta-analysis of prevalence, determinants, and health impacts in Egypt - Ahmed Azzam; Heba Khaled; Alrefaey K. Alrefaey; Amar Basil; Sarah Ibrahim; Mohamed S. Elsayed; Muhammad Khattab; Nashwa Nabil; Esraa Abdalwanees; Hala Waheed Abdel Halim (BMC Pregnancy and Childbirth)
Abstract Background The WHO considers anemia in pregnancy a severe public health issue when prevalence surpasses 40%. In response, we conducted a systematic review and meta-analysis to examine anemia among pregnant women in Egypt, focusing on its prevalence, determinants, and associated complications. Methods We conducted a systematic literature search for studies published between January 1, 2010, and August 18, 2024, to identify studies from Egypt reporting on anemia in pregnant women, including its prevalence, associated determinants, and complications. A meta-analysis was conducted using a random-effects model to estimate pooled prevalence, odds ratios (OR), and standardized mean differences (SMD). Sensitivity analyses and publication bias were performed. All statistical analyses were conducted using R software. Results Eighteen studies met the eligibility criteria with a total sample size of 14,548. The overall prevalence of anemia among pregnant women was 49% (95% CI: 42–57), with no significant difference between Upper and Lower Egypt (P = 0.66). The sensitivity analysis demonstrated the absence of influential outliers and Egger’s test indicated no evidence of publication bias (P = 0.17). Anemia prevalence was significantly higher in the third trimester (65%) compared to the second trimester (47%) (P = 0.03). Among anemic pregnant women, most cases were mild (47%) and moderate (47%). The determinants of anemia among pregnant women included being over 30 years old (OR: 1.95), residing in rural areas (OR: 1.76), illiteracy (OR: 1.93), birth spacing < 2 years (OR: 2.04), lack of iron supplementation (OR: 2.59), presence of intestinal parasites (OR: 1.38), antenatal visits < 5 (OR: 5.27), multiparity, and low income, all with statistical significance (p < 0.05). Regarding dietary determinants, a low intake of meat, vegetables, fruits, and high tea consumption was consistently associated with a higher risk of anemia. For neonatal complications, infants born to anemic mothers had significantly lower Apgar scores, gestational ages, and birth weights (P < 0.05), with birth weight being the most adversely impacted (SMD = -1.3). Conclusions This meta-analysis shows 49% anemia prevalence in pregnant Egyptian women, indicating severe health concern. The findings highlight the urgent need for targeted interventions aimed at addressing the key determinants identified in this study.